An Evaluation of Nursing Specialty Program in Nursing Administration, revised 2015, The Royal Thai Army Nursing College - Akathin, Sirinya; Ounjaichon, Sasiporn; Siripukdeekan, Chayaluck (Journal of The Royal Thai Army Nurses, 2021)
This study aimed to evaluate the Nursing Specialty Program in Nursing Administration, revised 2015, the Royal Thai Army Nursing College, in Context, Input, Process, and Product. The samples were 103 graduates from the Nursing Specialty Program in Nursing Administration Batch 12-15. The questionnaires were developed by the researchers which reliability determined by Cronbach’s alpha was at .82. Quantitative data were analyzed using mean, standard deviation and One-way Analysis of Variance: One-way Anova. Qualitative data were analyzed using content analysis. The results of the research were as follows: The overall program evaluation was in high level for all dimensions ( = 4.24, SD = 0.63). The opinions of graduates from the Nursing Specialty Program in Nursing Administration Batch 12-15 towards the program in relation to context, input, process and product were not statistically significantly different (p<.05). The strengths of the program highlight three issues, including the contents of the program, instructors, and the application of the knowledge gained from the program. Suggestions include program management, skills/qualifications to be further develop, and learning facilities/ study visits. Therefore, it would be advantageous for program coordinators to apply this study as a guideline to further develop/revise the program to be updated and relevant to learners’ needs, resulting in great benefits for learners and their institutions.